Preparation method of biomass hard carbon negative electrode material of sodium ion battery
Sodium ion battery biomass hard carbon material is prepared by controlling the feed component ratio and using zinc gluconate to control the surface morphology, solving the problem of insufficient hard carbon surface structure treatment in the prior art, and achieving low-cost and high-performance material preparation.
Patent Information
- Application Number
- CN202510005737.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
There are fewer processing techniques for existing sodium ion battery negative electrode materials, especially the treatment of hard carbon surface structures, which affects the electrochemical performance and industrial application of the materials.
Sodium ion battery biomass hard carbon negative electrode material is prepared by controlling the proportion of feed ingredients to feed insects as raw materials, zinc gluconate is used as feed additives to control the surface morphology of hard carbon, and porous hard carbon materials are prepared through low-temperature pre-carbonization and high-temperature carbonization steps.
It has achieved the preparation of low-cost, controllable surface structure of sodium ion battery biomass hard carbon materials, with excellent electrochemical performance and commercialization potential, and is suitable for large-scale production.
Smart Images

Figure CN119797325A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery negative electrode materials, and relates to a method for preparing a sodium ion battery biomass hard carbon negative electrode material, and specifically relates to a method for preparing a sodium ion battery biomass hard carbon negative electrode material by using the feces of insects fed with a controlled feed ingredient ratio as a raw material. Background Art
[0002] With the continuous growth of global energy demand and the increasingly severe environmental problems, the development of efficient and sustainable energy storage technology has become an important direction of current scientific research. As the most widely used energy storage device, lithium-ion batteries have gained a huge market share in consumer electronics, electric vehicles and other fields by virtue of their excellent energy density and cycle performance. However, the limited lithium resources, price fluctuations and their environmental impact have prompted the research and development of sodium-ion batteries as an alternative. The abundance of sodium in the earth's crust is high, the price is low and environmentally friendly, so sodium-ion batteries are regarded as potential candidates for future energy storage technology. Biomass hard carbon is one of the candidates for sodium-ion battery negative electrode materials because of its low cost. However, there are very few treatments for the surface structure of hard carbon. Therefore, the present invention uses the feces of insects fed with controlled feed ingredients as raw materials to prepare sodium-ion battery biomass hard carbon negative electrode materials with excellent electrochemical properties and controllable surface morphology, which have great commercial potential. Summary of the invention
[0003] The present invention aims to improve the existing process and provide a new method for preparing sodium ion battery biomass hard carbon negative electrode material by using the excrement of insects fed with controlled feed ingredient ratio as raw material, which is low-cost and easy to industrialize.
[0004] The present invention uses corn flour and zinc gluconate as feed, controls the proportion of feed ingredients, and collects waste feces generated by insect farming to prepare biomass hard carbon negative electrode materials. Since insect feces are a byproduct of insect farming, it has a huge advantage of very low manufacturing cost, and the surface morphology of hard carbon can be controlled according to the amount of zinc gluconate added, and has the characteristic of controllable surface morphology.
[0005] The technical solution of the present invention is described in detail below.
[0006] A method for preparing a sodium ion battery biomass hard carbon negative electrode material, the method is a method for preparing a sodium ion battery biomass hard carbon negative electrode material by using the excrement of insects fed with a controlled feed ingredient ratio as a raw material, and the specific preparation method comprises the following steps:
[0007] S1, feeding insects with feed, and then collecting insect feces; the feed includes insect feed raw materials and zinc gluconate;
[0008] S2, pre-carbonizing the collected insect feces at low temperature under inert gas;
[0009] S3. After carbonization, the product is collected, and after acid washing and drying, the material is carbonized at high temperature under inert gas to finally obtain a hard carbon material.
[0010] The present invention uses zinc gluconate as a feed additive to feed insects, so that the insects can ingest zinc and excrete it with feces. Subsequently, zinc oxide is generated under the action of pre-carbonization to serve as a pore-forming agent, thereby facilitating the acquisition of a porous hard carbon material. The surface structure of the hard carbon material can be controlled by controlling the conditions.
[0011] Preferably, the insect feed raw material in step S1 is corn flour. By using corn flour as the feed raw material, the insects mentioned in the present invention have better palatability, and can further ensure that the insects eat it cleanly, thereby ensuring that the collected insect feces are not mixed with the feed.
[0012] Preferably, in step S1, the feed is mixed with water into a ball and then fed, which is more conducive to evenly mixing the insect feed raw materials and zinc gluconate and allowing all insects to eat them.
[0013] Preferably, the mass ratio of the insect feed raw material to zinc gluconate in step S1 is 100:(2.5-30). More preferably, the mass ratio of corn flour to zinc gluconate is 100:10.
[0014] Preferably, the insects described in step S1 include but are not limited to at least one of mealworms, wax moth larvae, locusts, crickets, black soldier fly larvae, cockroaches, etc. More preferably, the experimental insects described in step S1 are cockroaches.
[0015] Preferably, the low-temperature pre-carbonization temperature in step S2 is 400-700°C, the heating rate is 1-10°C / min, and the holding time is 0.5-4 hours. More preferably, the pre-carbonization temperature in step S2 is 600°C, the temperature is kept for 2 hours, and the heating rate is 5°C / min. Pre-carbonization allows the zinc in insect feces to generate zinc oxide inside and on the surface of the carbon at this temperature, thereby preparing in advance for the next step of generating porous hard carbon. The temperature, rate, and time will affect the amount and size of zinc oxide. Under the conditions of the present invention, a suitable product can be obtained, thereby having better performance.
[0016] Preferably, the inert atmosphere in step S2 and step S3 is at least one of nitrogen, helium and argon.
[0017] Preferably, the pickling in step S3 is performed with hydrochloric acid, the concentration of the hydrochloric acid is 0.5-5 mol / L, and the pickling time is 0.5-12 h; more preferably, the concentration is 1 mol / L, and the pickling time is 3 h.
[0018] Preferably, the acid washing in step S3 further includes water washing and filtering.
[0019] Preferably, the drying in step S3 is performed at 70°C.
[0020] Preferably, in step S3, the high-temperature carbonization temperature is 900-1600°C, the holding time is 0.5-4 hours, and the heating rate is 1-10°C / min. More preferably, in step S3, the carbonization temperature is 1400°C, the holding time is 2 hours, and the heating rate is 5°C / min. High-temperature carbonization conditions have an impact on the performance of the hard carbon material, and the performance of the hard carbon material is better under the conditions in the range.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a method for preparing a low-cost, surface-structure controllable sodium-ion battery biomass hard carbon material: the raw materials of the method are byproducts of insect breeding, the cost is extremely low, and the surface structure of the hard carbon material can be controlled by controlling the content of zinc gluconate in the feed, thereby meeting different application requirements. The green, environmentally friendly, and highly cycle-stable sodium-ion battery biomass hard carbon negative electrode material preparation method of the present invention has the characteristics of being able to be mass-produced, having diverse hard carbon surface morphologies, and having excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the X-ray diffraction pattern (XRD pattern) of the hard carbon material prepared in Examples 1 and 2.
[0024] Figure 2 This is a scanning electron microscope (SEM) photograph of the hard carbon material prepared in Example 1.
[0025] Figure 3 This is a scanning electron microscope (SEM) photograph of the hard carbon material prepared in Example 2.
[0026] Figure 4 The cycle performance of the hard carbon materials prepared in Examples 1 and 2 at a current density of 0.05 A / g.
[0027] Figure 5 The cycling performance of the hard carbon materials prepared in Examples 1 and 2 at a current density of 1 A / g. DETAILED DESCRIPTION
[0028] In order to better clarify and understand the purpose, process scheme and advantages of the present invention, the technical scheme and implementation method of the present invention are further described clearly, completely and in detail through specific examples and in combination with the accompanying drawings. It should be noted that the embodiments described in the present invention are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given, but they are only part of the embodiments of the present invention, not all of the embodiments. The specific implementation methods described are limited to explaining and interpreting the present invention, and do not limit the present invention. Based on the embodiments in the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0029] The experimental methods and conditions used in the embodiments of the present invention are conventional methods and conventional conditions unless otherwise specified. The materials, reagents or instruments used in the embodiments, unless otherwise specified, can be obtained from commercial sources or prepared by conventional methods. The reaction conditions embodied in the content of the invention of the present invention can achieve the reaction and obtain the product of the expected effect. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of the present invention.
[0030] Embodiment 1:
[0031] Corn flour and zinc gluconate were mixed in a ratio of 100:2.5, and a small amount of hot water was added to mix them into a mass. The feed was then fed to cockroaches. After the cockroaches ate the feed, the remaining feces of the cockroaches were collected; the collected cockroach feces were pre-carbonized by heating to 600°C at 5°C / min under argon and kept warm for 2 hours; the product was collected after carbonization, and was acid-washed with 1mol / L hydrochloric acid for 2 hours, washed with ultrapure water for 3-4 times, and then filtered, and finally dried at 70°C; the dried material was carbonized by heating to 1400°C at 5°C / min under argon and kept warm for 2 hours, and finally a hard carbon material was obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0032] Embodiment 2:
[0033] After corn flour and zinc gluconate are mixed in a ratio of 100:10, a small amount of hot water is added to mix them into a mass, and then the feed is fed to cockroaches. After the cockroaches eat the feed, the remaining feces of the cockroaches are collected; the collected cockroach feces are pre-carbonized by heating to 600°C at 5°C / min under argon and kept warm for 2 hours; the product is collected after carbonization, washed with 1mol / L hydrochloric acid for 2 hours, washed with ultrapure water 3-4 times, and then filtered, and finally dried at 70°C; the dried material is heated to 1400°C at 5°C / min under argon for carbonization, and kept warm for 2 hours, and finally a hard carbon material is obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0034] Embodiment 3:
[0035] After corn flour and zinc gluconate are mixed in a ratio of 100:30, a small amount of hot water is added to mix them into a mass, and then the feed is fed to cockroaches. After the cockroaches eat the feed, the remaining feces of the cockroaches are collected; the collected cockroach feces are pre-carbonized by heating to 600°C at 5°C / min under argon and kept warm for 2 hours; the product is collected after carbonization, washed with 1mol / L hydrochloric acid for 2h, washed with ultrapure water 3-4 times, and then filtered, and finally dried at 70°C; the dried material is heated to 1400°C at 5°C / min under argon for carbonization, and kept warm for 2 hours, and finally a hard carbon material is obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0036] Embodiment 4:
[0037] After corn flour and zinc gluconate are mixed in a ratio of 100:2.5, a small amount of hot water is added to mix them into a mass, and then the feed is fed to mealworms. After the mealworms eat the feed, the feces left by the mealworms are collected; the collected mealworm feces are pre-carbonized at 5°C / min under argon and kept warm for 2 hours; the product is collected after carbonization, washed with 1mol / L hydrochloric acid for 2 hours, washed with ultrapure water for 3-4 times, and then filtered, and finally dried at 70°C; the dried material is heated to 1400°C at 5°C / min under argon for carbonization, and kept warm for 2 hours, and finally a hard carbon material is obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0038] Embodiment 5:
[0039] After corn flour and zinc gluconate are mixed in a ratio of 100:15, a small amount of hot water is added to mix them into a mass, and then the feed is fed to black soldier fly larvae. After the black soldier fly larvae eat the feed, the feces remaining in the black soldier fly larvae are collected; the collected feces of the black soldier fly larvae are pre-carbonized by heating to 600°C at 5°C / min under argon and kept warm for 2 hours; the product is collected after carbonization, and is acid-washed with 1mol / L hydrochloric acid for 2 hours, washed with ultrapure water for 3-4 times, and then filtered, and finally dried at 70°C; the dried material is heated to 1400°C at 5°C / min under argon for carbonization, and kept warm for 2 hours, and finally a hard carbon material is obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0040] Embodiment 6:
[0041] After corn flour and zinc gluconate are mixed in a ratio of 100:5, a small amount of hot water is added to mix them into a mass, and then the feed is fed to locusts. After the locusts eat the feed, the remaining feces of the locusts are collected; the collected locust feces are pre-carbonized at 5°C / min under argon and kept warm for 2 hours; the product is collected after carbonization, washed with 1mol / L hydrochloric acid for 2 hours, washed with ultrapure water 3-4 times, and then filtered, and finally dried at 70°C; the dried material is heated to 1400°C at 5°C / min under argon for carbonization, and kept warm for 2 hours, and finally a hard carbon material is obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0042] Embodiment 7:
[0043] After corn flour and zinc gluconate are mixed in a ratio of 100:5, a small amount of hot water is added to mix them into a mass, and then the feed is fed to the wax moth larvae. After the wax moth larvae eat the feed, the feces of the wax moth larvae are collected; the collected wax moth larvae feces are pre-carbonized at 5°C / min under argon and kept warm for 2 hours; the product is collected after carbonization, washed with 1mol / L hydrochloric acid for 2 hours, washed with ultrapure water for 3-4 times, and then filtered, and finally dried at 70°C; the dried material is heated to 1400°C at 5°C / min under argon for carbonization, and kept warm for 2 hours, and finally a hard carbon material is obtained. The specific surface area and pore volume of the material are shown in Table 1.
[0044] Table 1 Summary of specific surface area and pore volume of hard carbon materials in various examples
[0045]
[0046] From the above, it can be seen that the hard carbon prepared by using cockroach feces in Examples 1-7 has a higher specific surface area and is the most preferred for insects. In Examples 1, 2, and 3, the more zinc gluconate is added, the larger its pore volume will be. The optimal zinc gluconate addition amount is 10%, which has the largest specific surface area and is the most preferred zinc gluconate addition amount.
[0047] The above-described embodiments are only preferred solutions of the present invention and are not intended to limit the present invention in any form. There are other variations and modifications without exceeding the technical solutions described in the claims.
Claims
1. A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1, feeding insects with feed, and then collecting insect feces; the feed includes insect feed raw materials and zinc gluconate; S2, pre-carbonizing the collected insect feces at low temperature under inert gas; S3. Collect the product, wash it with acid, dry it, and then carbonize it at high temperature under inert gas to obtain a hard carbon material.
2. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: The insect feed raw material in step S1 is corn flour.
3. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the insect feed raw material to zinc gluconate in step S1 is 100:(2.5-30).
4. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: The insects described in step S1 are selected from at least one of mealworms, wax moth larvae, locusts, crickets, black soldier fly larvae, and cockroaches.
5. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the temperature of low-temperature pre-carbonization is 400-700°C, the holding time is 0.5-4 hours, and the heating rate is 1-10°C / min.
6. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 5, characterized in that: In step S2, the pre-carbonization temperature is 600°C, the temperature is kept for 2 hours, and the heating rate is 5°C / min.
7. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: The pickling in step S3 uses hydrochloric acid with a concentration of 0.5-5 mol / L, and the pickling time is 0.5-12 h.
8. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: The drying in step S3 is performed at 70°C.
9. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the temperature of high temperature carbonization is 900-1600° C., the holding time is 0.5-4 hours, and the heating rate is 1-10° C. / min.
10. The method for preparing a sodium ion battery biomass hard carbon negative electrode material according to claim 9, characterized in that: In step S3, the carbonization temperature is 1400° C., the temperature is kept for 2 hours, and the heating rate is 5° C. / min.
Citation Information
Patent Citations
Preparation method of graphene feeding silkworm dropping active carbon and silkworm dropping active carbon
CN107651686A
Lithium-sulfur battery positive electrode material and preparation method thereof
CN109494366A
Tenebrio molitor dung biochar as well as preparation method and application thereof
CN113860303A
Preparation method of porous hard carbon material for sodium-ion battery as well as product and application of porous hard carbon material
CN114988390A
Hard carbon negative electrode material and preparation method and application thereof
CN115571867A